Intellectual Property Protection in the Age of Digital Technology: Artificial intelligence as a model - ZAOUECHE, Chouaib; BELLAROU, Kamel (Journal of Human Sciences, 2025)
The development of information and communication technology has expanded the scope of intellectual property, resulting in what is known today as electronic or digital works, which include several types, the most prominent of which are programs, systems, and entities of artificial intelligence, which is a group of technologies whose use allows the system to perform tasks that usually require human intelligence. These revolutionary technologies have begun to challenge the traditional frameworks for protecting intellectual property, as they can access protected works and feed on them to enhance their self-learning without a license from their owners, and even allow others to access these works and view their content, which makes the issue of protecting intellectual property in light of these complex technologies limited, requiring its expansion through concerted international efforts to understand how these technologies work and establish agreements that regulate their development and public interaction with them.